A Clinical Study on the Treatment of Multiple Radial Fractures with Embedded Wearable Device Holder and Absorption Bone Nail Combined with Decoction. (4th March 2021) - Ren, Zhilong; Li, Xiangyang
Abstract : Multiple radial fractures have brought great pain to the patients, and the treatment takes a long time and the effect is slow, which seriously affects people's production and life. Traditional conservative treatment methods are mostly used for radius fractures. However, with the development of science and technology of the times, the level of medical treatment is also constantly improving. For radius fractures, the embedded wearable device fixation frame absorption bone nail treatment method has attracted attention. In order to study whether the embedded wearable device fixation frame can treat radius fractures, this article conducted a related survey of radius fracture patients in a hospital in a certain city, reviewed related literature, conducted interviews with professionals and so forth, and collected relevant information. A case template was constructed, and a clinical research model was created using a comprehensive quantitative and qualitative analysis method. The results of the study found that using the research embedded wearable device fixation frame to treat radius fractures with absorption bone nails can achieve good results, and its healing efficiency is about 20% faster than conservative treatment. With decoction, its treatment efficiency can be improved; and the prognostic treatment of the decoction can reduce the complications of the patient's treatment by about 13%. This shows that the embedded wearable device holder absorption bone nail combined with decoction can play an important role in the treatment of multiple radius fractures.